"And I'm in another world". A qualitative examination of the experience of participating in creative arts groups in Palestine. Issue 1 (2nd January 2021) - Soulsby, Laura K; Jelissejeva, Katerina; Forsythe, Alex
ABSTRACT: Background : We examine the experience of participating in creative arts groups for Palestinians living under the shadow of military conflict. Methods : 14 men and women aged 17–50 were recruited from community creative arts groups to participate in one of three semi-structured group interviews. Interviews explored participants' perceptions of the creative arts groups, including how they came to participate in the group and how they felt about their involvement. Results : An inductive thematic analysis identified three central themes: " An emptying", " Growth in the face of challenge", and " A rare freedom" . The themes capture the extreme challenges participants faced and the protective effects of the creative arts groups on wellbeing. Participating in creative arts activities, such as writing, drawing, and music, encourages self-expression and release, personal exploration and escapism. Conclusions : In the face of traumatic experiences, restrictions, and poverty associated with living in an occupied land, creative arts groups can be liberating and support wellbeing.